2006
DOI: 10.1191/0961203306lu2312oa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Cyclosporine A in the Treatment of Refractory Proteinuria in Childhood-Onset Lupus Nephritis

Abstract: We performed a prospective study to evaluate the efficacy and safety of low-dose cyclosporine A (CSA) treatment in paediatric lupus nephritis refractory to conventional therapy. Seven children with biopsy-proven Class III-IV lupus nephritis were treated with CSA (2-4 mg/kg/day) combined with low-dose prednisone for one year. All patients had failed to achieve sustained proteinuria remission with corticosteroids and cytotoxic drugs. Proteinuria decreased from median value of 2.5 g/24 hours (range, 1.2-4.9) to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
8
1
1
Order By: Relevance
“…As CD154 over-expression has a crucial role in the pathogenesis of SLE, our demonstration that NFAT mediates this over-expression in children renders CsA an attractive potential agent in the treatment of lupus. To date, the published experience with this agent in childhood SLE consists of two prospective studies (44, 45) and an open-randomized comparison of CsA versus corticosteroids plus cyclophosphamide (46), all of which showed varying degrees of improvement in disease manifestations, particularly proteinuria. The lack of a controlled clinical trial of this medication in lupus likely reflects its adverse effect profile, which consists of nephrotoxicity and reversible hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…As CD154 over-expression has a crucial role in the pathogenesis of SLE, our demonstration that NFAT mediates this over-expression in children renders CsA an attractive potential agent in the treatment of lupus. To date, the published experience with this agent in childhood SLE consists of two prospective studies (44, 45) and an open-randomized comparison of CsA versus corticosteroids plus cyclophosphamide (46), all of which showed varying degrees of improvement in disease manifestations, particularly proteinuria. The lack of a controlled clinical trial of this medication in lupus likely reflects its adverse effect profile, which consists of nephrotoxicity and reversible hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also shown improvement in proliferative nephritis with the use of cyclosporine and tacrolimus. However, relapses were found to be common after discontinuation [44,45].…”
Section: Management Of Nephritismentioning
confidence: 97%
“…HLA DRB1*03:01, DQA1*05:01, and DQB1*02:01 are more common in Caucasians with SLE, again independent of age at disease onset121. Non-MHC loci that have been associated with pediatric SLE and aSLE are the 1858T single nucleotide polymorphism (SNP) of PTPN22, a gene which encodes for the enzyme lymphocyte phosphatase (Lyp) and inhibits T-cell activation116, 122123. A polymorphism (−28C/G polymorphism) of the RANTES (also CCL5) gene also has been associated with aSLE, and its importance was confirmed in a study of Chinese children with SLE124.…”
Section: Geneticsmentioning
confidence: 99%